Efficiency, Competitiveness And Resilience Of Banking: A Systematic Literature Review - Sylvia; Maarif, Mohammad Syamsul; Hermadi, Irman; Asikin, Zenal (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to analyze and classify the literature on efficiency, competitiveness and resilience of banking systems. The banking sector remains in a state of development, contending with problems including heightened competitiveness, regulatory pressures, and technological advancements. By sustaining equilibrium among efficiency, competitiveness, and resilience, banks can persist in flourishing within a dynamic environment. Methodology/ Approach: by conducting literature studies published between 2015-2023 in the journal listed in the Journal Citation Report. It is then analyzed according to a systematic literature review approach involving interpretation-based assessments of research methodologies and critical findings in the study. Findings: The direction of this research is expected in the future to have implications for academics and practitioners. This study found that Resilience is essential for banks to successfully confront the difficulties and hazards that periodically emerge. Practical Implications: Banks must consistently prioritize enhancing their resilience by formulating effective strategies and perpetually fortifying their security systems and adherence to relevant norms and regulations. Originality/value: This study indicates varios way to analyzing the elements, tactics, and regulations necessary to achieve banking efficiency, competitiveness, and resilience.